Bibliometric Analysis of Research on Factors Affecting Service Quality and Physician Performance - Marlina Marlina; Iwan Aflanie; Izaak Zoelkarnain Akbar; Muhammad Abdan Shadiqi; Ardik Lahdimawan (Malahayati Nursing Journal, 2024)
ABSTRACTThis study analyzes the influence of various factors on service quality and doctor performance with a focus on aspects of additional employee income, adequacy of doctor personnel, facilities and infrastructure, competence, and communication. The background of this study is the importance of improving the quality of health services to achieve optimal patient satisfaction and effective physician performance. The purpose of this study is to identify trends, distribution, and relationships between these factors in the scientific literature, as well as identify research gaps that need to be further explored. The method used in this study is bibliometric analysis, with data collected from Google Scholar using the Publish or Perish application. The search period was limited to 2018 to 2024, and the keywords used included "quality of service," "performance," "doctors," "factors," "facilities and infrastructure," "income," "competence," and "communication." The data was analyzed using VOS viewer to visualize the keyword network and identify research trends.The results show that India and Indonesia are the biggest contributors with 10 and 5 publications respectively. Springer and Emerald were the most active publishers, with 9 and 8 publications respectively. The publication trend peaked in 2019 with 16 publications, and the citation analysis identified the article "Health care service delivery based on the Internet of things: A systematic and comprehensive study" as the most influential with 249citations. Network visualization revealed close relationships between keywords such as "doctor," "service quality," and "competence." The conclusion of this study is that although there are many studies that discuss factors affecting service quality and physician performance, there are still gaps that need to be further explored, especially regarding the influence of additional employee income, adequate physician staffing, and facilities and infrastructure. Filling these gaps will provide a more comprehensive understanding and help improve the overall quality of healthcare services.Keywords: Service Quality, Doctor Performance, Competence, Communication, Infrastructure.